Effects of local institutions on the adoption of agroforestry innovations: Evidence of farmer managed natural regeneration and its implications for rural livelihoods in the Sahel - Binam, Joachim N.; Place, Frank; Djalal, A.A.; Kalinganire, A. (Springer, 2017)
The present study aims at (1) assessing how the existing local formal and informal institutions affect farmer managed natural regeneration (FMNR) practices and, (2) evaluating the benefits of such practices on livelihoods. The propensity score with continuous treatments was used to assess the effects of a set of covariates on FMNR as well as the impacts of that practice on income, cereal production and caloric intake using data collected from 1,080 rural households in Burkina Faso, Mali, Niger, and Senegal. This study demonstrated that regeneration of trees on farms, whereby farmers play an active role in the types of trees and their densities, is important as a practice and safety-net by providing cash income, caloric intake and diet, and crops supplements throughout dryland areas of West Africa. Overall, FMNR cannot be excluded as a recommendation in any geographical region. In addition, the study concludes that the effects of institutions in fostering FMNR practices in the Sahel are mixed. In areas with well-structured formal and informal institutions, populations seem to have adopted a better collaboration attitude with the local government by developing plans for a good management and protection of natural resource including FMNR practices. However, in areas where these commissions are being assimilated to governmental institutions, the willingness to raise incentives towards a better management of natural resources is less perceived. While recognizing the benefits of trees and tree products on caloric intake and diet, there is a need to explore in much more details, the FMNR-food nexus in future researches by going beyond what was covered from this study.